Recent Advances in Multifunctional Microneedle Patches for Wound Healing and Health Monitoring. Issue 2 (30th December 2022) - Pan, Panpan; Liu, Qing; Wang, Lin; Wang, Chunxiao; Hu, Le; Jiang, Yongjian; Deng, Yonghui; Li, Guisheng; Chen, Jingdi
Abstract : Benefiting from the advantages of minimal invasiveness, painlessness, and ease to use, microneedle patches (MPs) have been extensively studied in the biomedical field through a physical penetration enhancement pathway. This study systematically summarizes the preparation methods, function optimization, and diagnostic and therapeutic applications of MPs. First of all, the raw materials and methods commonly used in different preparation processes for MPs are highlighted. Then, the corresponding solutions to the problems facing MPs, such as poor tissue adhesion, weak mechanical strength, and low drug delivery utilization in their development and application, are emphasized, which serve as approaches to improve the performance of MPs. Subsequently, the latest applications of MPs for wound healing and health monitoring in recent years are summarized in‐depth, revealing the unique merits of MPs in diagnosis and treatment. Finally, the key points for the urgent improvement of MPs in clinical translation and commercial application are deliberated, in order to inspire the future direction of multifunctional and intelligent MPs. Abstract : Microneedle patches (MPs), an emerging technology for physically enhancing the transdermal absorption of drugs, are particularly crucial for the rational selection of materials and preparation processes. Various strategies to improve their adhesion, mechanics, and drug utilization are critically reviewed with an aim to guide the future development of wearable MP‐based systems with integrated diagnosis and therapy functions in clinical medicine.